Incongruencia del art. 16.1 del código del trabajo en el contrato de servicio determinado dentro del giro del negocio, en relación a la terminación de la relación de trabajo y el pago de la bonificación por desahucio - Chanaluisa Cuyachamin, Wilmer Neptali (2017)
The Organic Law for Labor Justice and Labor Award in the Home, reformed the Art. 14 of the Labour Code eliminating fixed-term contracts, which could be agreements up to one year, renewable for another year, this is due to the need to prevent the widespread practice of employers to replace workers at the end of the agreed period, so do not accumulate seniority in the company. This article determines the individual employment contract to indefinite is the typical mode of stable or permanent employment contracts. The elimination of fixed-term contracts has the disadvantage also not consider the particular circumstances of the companies, which at certain times, due to the peculiarities of production requires more workers, if not permanently. Art. 16.1 of the Labour Code establishes the type of contract called contract of work or service within the line of business, that something can alleviate the effects of the elimination of the forward contract, which is to allow the hiring of workers without the overall stability for the execution of a work or service, after which the contract will terminate upon payment of a situation similar to that established for the eviction bonus, 25%. An existing incongruity between the effects of such contracts, on the one hand it is argued that the contract ends and the other parties subsists post contractual effect is observed. It is more contrary to Art. 170 of the Labour Code which can not be forced eviction by the end of the work period of work or services covered by the contract, which to be a post contractual effect leads to their determined illegal by law.